Pastiche as the aesthetic of postmodernism in Jessica Hagedorn's dogeaters - Yapo, Jerry R. (UP Los Baños Journal, 2008)
Jessica Hagedorn is considered as one of the more prolific and critically acclaimed Filipino writers today. She is based in the United States. Dogeaters is Hagedorn's first novel and one of the few contemporary writings by a Filipino woman that is extensively reviewed and patronized here and abroad. A reading of dogeaters was done to determine how a postmodern/postcolonial text appropriates pastiche as its mode of rendering an experience. The novel's 1991 Pandora press edition was examined. It is observed that pastiche is evident in the images cut and pasted on the cover and the bits and pieces of the narrative presented in the text. The entire material emerges as one aesthetic rendering the Philippine experience and succeeds semanticizing certain historical realities.